A Prospective Comparative Study on Metabolic Syndrome Among Urban and Rural Women Population- A Cross Sectional Study (Academia Journal of Medicine, 2020)
Background: Metabolic syndrome is a combination of individual risk factors that are associated with several serious health conditions such as diabetes, cardiovascular disease or stroke. The present study was conducted to assess metabolic syndrome among urban and rural women population. Subjects and Methods: 128 females diagnosed with metabolic syndrome were included. Smoking, drug history, past history, family history etc. was taken. Weight, height, BMI, waist circumference, hip circumference, waist to hip ratio, systolic and diastolic blood pressure was also recorded. Results: Age group 20-35 years comprised of 24, 35-50 years had 36 and >50 years had 68 patients. The socio- economic status was middle in 70 and upper in 58, education was primary in 45 and high in 73, occupation was unemployed in 80 and employed in 48. Smoking was seen in 52 (40.6%), hypertension in 78 (60.9%), Hypertriglyceride in 84 (65.6%), alcoholics in 40 (31.2%), increased FBS in 102 (79.6%) and low HDL in 80 (62.5%). Conclusion: Maximum women with MS was seen in age group >50 years. Smoking, hypertension, hypertriglyceride, alcoholism, increased FBS and low HDL was seen in all patients.
Keywords: Metabolic syndrome; Smoking; Hypertension